Problematic Gaming and Internet Use but Not Gambling May Be Overrepresented in Sexual Minorities – A Pilot Population Web Survey Study - Broman, Niroshani; Hakansson, Anders (Frontiers in Psychology, 2018)
Background Substance-related addictive disorders are known to be overrepresented in non-heterosexual individuals, but it is largely unknown whether this is also the case for behavioural addictions such as problem gaming and gambling. This study aimed, in a pilot web survey design, to assess whether problematic gambling, gaming and internet use may be more common in sexual minorities. Methods An online survey was distributed through media and social media, and answered by 604 individuals (51% women, 11% non-heterosexual). Problem gambling, problem gaming and problematic internet use were measured through structured screening instruments (the CLiP, the GAS and the PRIUSS, respectively). Results Problem gaming and problematic internet use were significantly more prevalent in non-heterosexual subjects. Instead, problem gambling did not differ between heterosexual and non-heterosexual respondents. Psychological distress and social media use for more than three hours daily were significantly more common in non-heterosexual respondents. In the overall sample, gaming and gambling were associated statistically. Conclusion Based on the present pilot online survey, problematic gaming and internet use, but not problem gambling, may be more common in sexual minorities. This area merits more and larger studies, and potentially preventive efforts aimed for non-heterosexual individuals in the population. Possible explanations and study limitations are discussed in the paper.